Balancing access with accuracy for infant HIV diagnostics in Tanzania (A) - Palamountain, Kara, (SAGE knowledge. Cases., 2016)
The Global Health Initiative (GHI) is a tripartite collaboration among Northwestern University, non-profit donors, and commercial diagnostics companies. GHI attempts to bridge the gap between the market for sophisticated medical diagnostics equipment in wealthy nations and the need for point-of-care diagnostics in resource limited settings. In 2006 GHI narrowed its focus to HIV diagnostics for underserved nations. The case examines the accuracy-access trade-off related to the roll-out of infant HIV diagnostics in Tanzania.